Digital Transformations in Modern Supply Chains: An Integrated Analysis - Alisa-Mihaela AMBROZIE; Ionel Sergiu PIRJU; Sergiu-Lucian SORCARU (Communications of International Proceedings, 2023)
The modern landscape of international trade and supply chains is undergoing a significant transformation, driven by the advent of digital innovations. These changes, while essential for enhancing operational efficiency, also bring forth critical issues related to sustainability, transparency, and traceability. This article offers an in-depth analysis of how digital technologies are actively redefining supply chains. By referencing recent studies, we delve into the crucial aspects of energy efficiency, product traceability, and the wider effects of supply chain digitization. The incorporation of these digital tools not only optimizes operations but also fosters greater confidence among stakeholders, all while addressing the urgent need for sustainability. This study seeks to provide a thorough understanding of the digital progression within supply chains and to critically examine the implications of adopting such technologies for both businesses and consumers.
Keywords: supply chain; digitalization; sustainable transformation; influence; strategy